Screening for microbial load and antibiotic resistance pattern in Escherichia coli isolated from paper currency circulating in Kushtia, Bangladesh - Rahman, S. M. Raihan; Uddin, Md. Nazim; Nain, Zulkar; Karim, Mohammad Minnatul (International Journal of Research in Medical Sciences, 2019)
Background: Paper currency is used for every type of commerce and plays an important role in the life of human beings. They are exchanged and come into contact with different environments and many different individuals during their circulation. Therefore, they can become contaminated with microorganisms and transfer bacteria across environments. The present study was aimed for quantitative assessment of microorganisms in circulated paper currency from Kushtia, Bangladesh and antibiotic resistant profiles of isolated Escherichia coli. Methods: A total of 10 paper currency samples currently in circulation involving three denominations (5, 10 and 500) were randomly collected from individuals involved in various occupations including street beggar, local hotel, bus conductor, poultry seller, vegetable seller, fish seller, commercial bank, ATM booth, tea seller, grocery store in Kushtia city, Bangladesh. Selective culture and biochemical tests were performed for the isolation and identification of microbial pathogens. Antibiotic resistance profiles were evaluated for isolated Escherichia coli using Kirby-Bauer method according to CLSI guidelines. Results: Aerobic mesophilic bacteria, Enterobacteriaceae and Pseudomonas spp. were the highest in paper currency from local hotel and ATM booth. Enterobacteriaceae (including coliforms) were predominantly present in paper currencies collected from local hotel, grocery, fish seller and beggar while Pseudomonas spp. were found in currency notes obtained from ATM booth, poultry farm, vegetable seller and local hotel. Antibiotic resistant profiles of E. coli isolated from local hotel currency showed that 50% of E. coli isolates were multidrug resistant. The highest resistant profile was observed against penicillin (95%) followed by polypeptide (75%), cephalosporin (50%), quinolone (30%) and sulfonamide (5%) groups of antibiotics. Conclusions: Multiple antibiotic resistant pathogenic bacteria are prevalent in paper currency regardless of their sources. Paper currency could contribute in transmission of infectious disease as well as in antibiotic resistance, therefore, should be handled carefully.